Optimization of Pretreatment and Hydrothermal Process of Na-X Zeolite from Kaolin and Metakaolin - Hartati Hartati; Satya Candra Wibawa Sakti; Putri Bintang Dea Firda; Chabibah Saidah (Jurnal Kimia Valensi, 2019)
Synthesis of Na-X zeolite was conducted from kaolin and metakaolin. Synthesis varied in its pretreatment method and hydrothermal conditions. The pretreatment methods used were: conventional alkaline, alkaline fusion and conventional fluoride. Hydrothermal conditions for the experiments were gradual temperature 40 oC  (6h), 60 oC (6h), 80 oC (12h), and constant temperature 80 oC for 24 h, 100 oC for 24 and 100 oC for 48 h. Synthesized products were characterized by X-Ray Diffraction (XRD), Fourier Transform InfraRed (FTIR), Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX), and N2 Isotherm Adsorption/Desorption method. The result showed that pre-treatment by conventional fluoride could not produce Na-X zeolite, synthesis by conventional alkaline and alkaline fusion with hydrothermal at 100 oC (48h), 100 oC (24 h), and gradual temperature produce Na-X zeolite with Na-P1 or Na-A zeolite as impurities, while synthesis from metakaolin by conventional alkaline with hydrothermal at 80 oC for 24 hours produced pure Na-X zeolite. Na-X zeolite and NaP1 zeolite with hierarchical pores were synthesized through alkali fusion with hydrothermal at 100 oC for 24 hours.